The Influence of Artificial Intelligence Skills and Strategic Management on the Business Performance of Food and Beverage Businesses in Upper Northern Thailand - คำขันแก้ว, พงศ์ศิริ; อารีย์, ราชัน; สมบูรณ์, ไอริน; วาริทธิ์, นิชาภรณ์; คนแรง, อารยา; จี้สอน, วิราพร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to examine the influence of Artificial Intelligence skills and strategic management on the business performance of food and beverage businesses in Upper Northern Thailand. This study employed a quantitative research approach. The sample consisted of 400 entrepreneurs operating food and beverage businesses in Upper Northern Thailand. A questionnaire was used as the research instrument. The research hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that the relationships among the variables show positive effects and are consistent with the proposed hypotheses. Artificial Intelligence skills have a very strong positive influence on strategic management (β = 0.862) and also have a direct positive influence on business performance (β = 0.608). At the same time, strategic management has a positive influence on business performance (β = 0.301). In addition, the results indicate that Artificial Intelligence skills have an indirect effect on business performance through strategic management (β = 0.260). This leads to a total effect of Artificial Intelligence skills on business performance of 0.867. Therefore, this study indicates that strategic management acts as a mediating variable between Artificial Intelligence skills and the business performance of food and beverage businesses in Upper Northern Thailand. The results of all three hypotheses are supported by empirical data.